Correlation between laboratory coagulation testing and thromboelastometry is modified during management of trauma patients. Issue 2 (August 2016) - David, Jean-Stéphane; Durand, Maeva; Levrat, Albrice; Lefevre, Mathilde; Rugeri, Lucia; Geay-Baillat, Marie-Odile; Inaba, Kenji; Bouzat, Pierre
Abstract : BACKGROUND: Thromboelastometry (ROTEM, Pentapharm GmbH, Munich, Germany) is increasingly being used to make a diagnosis of coagulopathy and to guide hemostatic therapy (HT). Although ROTEM parameters and standard laboratory test (SLT) correlated well before administration of HT, it is not known if this correlation persists after hemostatic resuscitation. METHODS: A retrospective analysis of prospectively collected data from a trauma registry (2011–2014) was performed. All patients having a ROTEM analysis were included. ROTEM parameters (clotting time and clot amplitude at 5 minutes) were determined after activation with tissue factor (EXTEM) or platelet inhibition with cytochalasin D (FIBTEM). Spearman rank correlation coefficient was calculated for the correlation between SLT and thromboelastometry parameters, and thresholds were determined with receiver operating characteristic (ROC) curve analysis for the diagnosis of an international normalized ratio (INR) greater than 1.5, fibrinogen 1.5 g/L or less, and platelet count of less than 100.10 9 /L. RESULTS: Of the 358 patients included, 533 thromboelastometry results were obtained (335 at admission, 198 during care). Correlation between INR and EXTEM–clotting time was good at admission ( r = 0.617) in the whole cohort but decreased in the subgroup of patients having an Injury Severity Score of less than 25 ( r = 0.399) or a base excess of less than 6 mmol/L ( r = 0.489). During care, correlation was impaired after the administration of fibrinogen concentrates in the whole cohort ( r = 0.430), as well as in the subgroup of patients having an Injury Severity Score greater than 24 ( r = 0.465). As well, for the diagnosis of increased INR, sensitivity and the area under the ROC curve decreased from 75% and 0.894 (no treatment) to 20% and 0.653 (fibrinogen concentrate). Areas under the ROC curve for the prediction of a fibrinogen or platelet decrease were not significantly altered regardless of the treatment group. CONCLUSIONS: A decrease in the correlation between SLTs and ROTEM parameters was observed at admission or during care, which could be in relation with injury severity, base deficit, or the administration of blood products, particularly fibrinogen concentrate. Further work will be necessary to better understand which tool is the most suitable for guiding HT. Level of Evidence: Therapeutic study, level IV; diagnostic study, level IV.